Disentangling Large- and Small-Scale Abiotic and Biotic Factors Shaping Soil Microbial Communities in an Alpine Cushion Plant System - Wang, Chenyue; Michalet, Richard; Liu, Ziyang; Jiang, Xingpei; Wang, Xiangtai; Zhang, Gaosen; An, Lizhe; Chen, Shuyan; Xiao, Sa (Frontiers in Microbiology, 2020)
Microorganisms play a crucial role in biogeochemical cycles and ecosystem processes, but the key factors driving microbial community structure are poorly understood, in particular in alpine environments. In this study, we aim to disentangle the relative contribution of abiotic and biotic factors shaping bacterial and fungal community structure at large and small spatial and integration scales in an alpine system dominated by a stress-tolerant cushion species. These effects were assessed in two mountain ranges of northwest China and for two contrasting phenotypes of the cushion species inhabiting two different microtopographic positions. Principal coordinate analysis, non-parametric multivariate analysis of variance and Variance partitioning analyses were conducted. Results indicated that large scale abiotic factors mainly affected bacterial community structure, whereas fungal community structure was mainly affected by biotic factors with an equal contribution of inter- and intra-specific effects. Future studies should analyse the direct factors contributing to shaping microbial community structure in particular at the intra-specific level.